Hedging Effectiveness and Optimal Hedge Ratios: An Analysis of Malaysian Crude Palm Oil Futures Market - OH, STELLA JIA XIN (2015)
This paper deals with the estimation of hedge ratios and hedging effectiveness of crude palm oil futures market in Malaysia for the period from January 2000 to August 2015. To measure hedging performances of optimal hedge ratio, different measures have been employed such as the static hedge ratio estimation models of conventional Ordinary Least Square (OLS) model and Vector Error Correction Model (VECM), while the time-varying model is presented by the Diagonal Vech Multivariate Generalized Autoregressive Conditional Heteroscedasticity (DVEC-MGARCH) model. Using daily spot and futures prices of crude palm oil which are traded on the Bursa Malaysia Derivatives Berhad, OLS regression model provides the largest variance reduction of the return portfolio. This result has been evidenced by many previous studies.